New Approaches in Photo-Bathymetry - H.-G. Maas; H. Sardemann; C. Mulsow; L.-A. Gueguen; G. Mandlburger (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences)
Stereo-Photogrammetric measurements under water with a camera placed outside the water requires modelling refraction. In the case of a wavy, non-stationary natural water surface, this spatio-temporal modelling may become rather complex. This paper will give a short overview on methods for instationary water surface consideration in photogrammetric approaches recently developed in a joint research project between TU Dresden and TU Wien. We first introduce a comprehensive and rigorous model which reconstructs the water surface with cubic splines and determines the underwater points in a simultaneous bundle block adjustment. In addition, we introduce an alternative approach to handle dynamic, wavy water surfaces based on image sequences. We show that by combining approximately 100 images taken at roughly the same position and orientation into a single image, the distortions of underwater objects caused by the wavy water surface can be largely mitigated. In the resulting image, the water surface appears smoothed, and the 3D reconstruction underwater can be performed as if the water surface were completely flat. The sequence-based approach can be formulated in image space and in object space. First results indicate a substantial accuracy increase of around an order of magnitude.